Evaluation of foot and ankle injuries in professional soccer: prospective analyses of the Paulista Soccer Championship 2016 - Kitagaki, Danilo Pizzo; Maciel, Eduardo Souza; Mansur, Nacime Salomão Barbachan; de Moraes, Eduardo Ramalho; Arliani, Gustavo Gonçalves (Journal of the Foot & Ankle, 2020)
Objective: To evaluate the profile of foot and ankle injuries in professional soccer. Methods: Data were collected prospectively during the 2016 São Paulo Soccer Championship using two electronic forms: an initial form (10 variables) and a follow-up form (6 variables). The results were standardized and evaluated in SPSS 23.0. Results: A total of 259 injuries were reported: 106 to the thigh (40.9%), 42 to the foot and ankle (16.2%), 39 to the knee (15.1%), 39 to the head or face (15.1%) and 33 in other locations (12.7%). Of the 42 foot and ankle injuries, 20 were lateral ankle sprains (47.6%), 5 were medial ankle sprains (11.9%), 3 were to the triceps surae (7.1%), 3 were leg contusions (7.1%), 3 were foot contusions (7.1%), 2 were myalgias (4.8%), in addition to 5 other types (11.9%). There was physical contact in 73.8% of the injuries (p <0.001), and six injuries (14.3%) were considered severe, i.e., involving a time loss of at least one month. Of the severe injuries, four were treated surgically (three by osteosynthesis and one by tenorrhaphy). The mean time loss due to injury was 19.7 days, and the overall incidence rate was 3.5 injuries per 1000 hours of exposure, with 2.1 ligament injuries per 1000 hours. X-rays and magnetic resonance imaging were the most requested tests in the follow-up of these patients. Conclusion: Foot and ankle injuries were the second most frequent injury in Brazilian professional soccer, 73.8% of which resulted from physical contact (p<0.001). Lateral ankle sprains accounted for 47.6% of these injuries, which reaffirms their high prevalence and importance for sports medicine. Level of Evidence III; Prognostic Studies; Prospective Study.